Integrated photoelectrochemical energy storage : solar hydrogen generation and supercapacitor - Zeng, Zhiyuan (2013)
Current solar energy harvest and storage are so far realized by independent technologies (such as solar cell and batteries), by which only a fraction of solar energy is utilized. It is highly desirable to improve the utilization efficiency of solar energy. Here, we construct an integrated photoelectrochemical device with simultaneous supercapacitor and hydrogen evolution functions based on TiO2/transition metal hydroxides/oxides core/shell nanorod arrays. The feasibility of solar-driven pseudocapacitance is clearly demonstrated, and the charge/discharge is indicated by reversible color changes (photochromism). In such an integrated device, the photogenerated electrons are utilized for H2 generation and holes for pseudocapacitive charging, so that both the reductive and oxidative energies are captured and converted. Specific capacitances of 482 F g−1 at 0.5 A g−1 and 287 F g−1 at 1 A g−1 are obtained with TiO2/Ni(OH)2 nanorod arrays. This study provides a new research strategy for integrated pseudocapacitor and solar energy application.